Development of a new general nuclide inventory analysis code GNIAC. (May 2018) - Ma, Jimin; Huang, Hongwen
Highlights: A new general nuclide inventory analysis code GNIAC has been developed. GNIAC applies both PFD and IPF forms of CRAM method as solver. GNIAC can read ENDF-6 format library and collapse GENDF with user-input neutron spectrum. GNIAC uses XML format for input and output files. The calculations of test cases validate the quality and correctness of GNIAC . Abstract: A new general nuclide inventory analysis code named GNIAC has been developed under the motivation of developing a modern and general-purpose tool to simulate nuclide transmutation process for nuclear applications. GNIAC applies both the Partial Fraction Decomposition (PFD) and Incomplete Partial Fraction (IPF) forms of Chebyshev Rational Approximation Method (CRAM) to solve inventory equations. It can read any nuclear evaluation library in ENDF-6 format and collapse fine-group GENDF data into single group cross sections with user-input neutron spectrum. The code adopts Extensible Markup Language (XML) format for input and output files, which makes the code user-friendly. Several modern programming techniques such as object-style, advanced source code management and version control have been applied. The present paper describes the status of the GNIAC code development and its validation which show that it is a useful nuclide inventory analysis tool for nuclear applications.